The Shakespeare Authorship Question: A Forensic Examination - Jimenez, Ramon (Journal of Scientific Exploration, 2023)
Most authorship disputes are between rival authors, between two or more writers for whom there is conflicting evidence within the works themselves, or conflicting testimony from others about who exactly composed what. The Shakespeare Authorship Question, however, is quite different. It is based on assumptions about the supposed author’s life, on a stunning absence of testimony by people who actually knew him, as well as silence by the author himself. That is, the traditional attribution is based on a lack of direct knowledge. Despite centuries of intense research and investigation, no credible evidence from his actual lifetime has emerged linking Will Shakspere of Stratford to the illustrious dramatic canon of the author who wrote under the pseudonym William Shakespeare. One major aspect of this search has been attempts by scholars to find individuals among Shakspere’s family, friends, and co-workers who spoke of him as a writer. It turns out that no one who lived and worked during the Stratford man’s dates ever did. Nor did he or any member of his family or his descendants ever claim that he was a writer. There is simply no contemporary record of anyone mentioning him in connection with playwriting. Even among the few literary men who were personally acquainted with him – poet and playwright Michael Drayton and historian William Camden to name two – neither ever mentioned him as a writer in their accounts of prominent men from the county of Warwickshire. Other residents of the Stratford area – some of whom were quite familiar with the London theatrical scene – never referred to him at all, much less as a dramatist. This included the theatergoer Edward Pudsey and the poet and playwright Fulke Greville, also Warwickshire residents. Dr. John Hall, who married Shakspere’s daughter Susanna in 1607, practiced medicine in Stratford for 30 years and wrote about his most interesting patients, never mentioned his father-in-law as a writer. This absence of direct knowledge and this absence of living testimony is unique in the history of authorship disputes. This article looks in detail at the silences of those around the Stratford man, people who should have mentioned his writing but didn’t, and ask what part such silence should play in knowledge formation.